2014
DOI: 10.1002/adfm.201400735
|View full text |Cite
|
Sign up to set email alerts
|

Large, Temperature‐Tunable Low‐Field Magnetoresistance in La0.7Sr0.3MnO3:NiO Nanocomposite Films Modulated by Microstructures

Abstract: 5393www.MaterialsViews.com wileyonlinelibrary.com environment. [ 9,10 ] Recently, due to the deepening cognition of the intrinsic and extrinsic GMR effect, growing attention has been paid to polycrystalline manganites to obtain the extrinsic low-fi eld magnetoresistance (LFMR) by structuring grain boundaries, nanosized inclusions, interface phase, and artifi cial grain boundaries. What's more, the LFMR in composites or fi lms can be further improved by introducing a secondary phase (usually non-magnetic or ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 64 publications
1
70
0
Order By: Relevance
“…It is noted that H C in particular shows a crossover at T B . This is in agreement with the experimental results in perovskite manganite in recent reports such as FM/AFM of La 1−x Ca x MnO 3 /La 1−y Ca y MnO 3 superlattices33, FM/PM of LSMO/LNO bilayers25, FM/AFM of LSMO/SrMnO 3 34 and LSMO/NiO composite films3536. This kind of thermal activation of the FM interactions across the interfaces has been proposed to manipulate the EB effect in the manganite systems.…”
Section: Resultssupporting
confidence: 92%
“…It is noted that H C in particular shows a crossover at T B . This is in agreement with the experimental results in perovskite manganite in recent reports such as FM/AFM of La 1−x Ca x MnO 3 /La 1−y Ca y MnO 3 superlattices33, FM/PM of LSMO/LNO bilayers25, FM/AFM of LSMO/SrMnO 3 34 and LSMO/NiO composite films3536. This kind of thermal activation of the FM interactions across the interfaces has been proposed to manipulate the EB effect in the manganite systems.…”
Section: Resultssupporting
confidence: 92%
“…It has been demonstrated that both microstructure and vertical strain play critical roles in controlling functionalities in nanoscaffolding films ( 30 ). Previous reports have focused on tuning MR by microstructure control ( 16 , 17 , 31 33 ). Hence, using the vertical strain to manipulate functionalities such as magnetic anisotropy, magnetism, and electron transport in ferromagnetic perovskite thick films has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…La 0.7 Sr 0.3 MnO 3 (LSMO) is selected as the matrix for this 3D strain design as it has shown a strong CMR effect, magnetic anisotropy, spin-glass like behavior, and LFMR properties. 11,22,36,37 Various secondary phases have been demonstrated for enhanced LFMR in LSMO VAN films. 19,[36][37][38][39] CeO 2 is selected as the insulating secondary phase embedded in the LSMO matrix, because of its good in-plane lattice match with LSMO and STO after a 451 in-plane rotation ( Fig.…”
Section: Conceptual Insightsmentioning
confidence: 99%
“…Such ratio was selected based on the previous reports where effective tunneling effects from the secondary phase have been found. 27,36,37,40 This set of interlayered samples are expected to combine the vertical strain control by the VAN structures and the lateral strain control by the interlayers to achieve 3D strain modulation. LFMR properties are measured and correlated with the strain in these 3D strained frameworks.…”
Section: Conceptual Insightsmentioning
confidence: 99%